(untitled) (Bangladesh Journal of Animal Science, 2013)
An experiment was conducted to determine the impact of Plantain (PL), Bio-Sel-E and commercial broiler diet on the growth performance, feed conversion ratio, performance index and carcass yield of broiler. A total of 160 day old broiler chicks (Cobb-500) were randomly distributed into four groups with four replication in each group and having 10 birds in each replication. Basal diet was used for group 1 (control), Basal diet was supplemented with PL (0.5% of DM basis) and Bio-Sel-E (5g/50 birds in drinking water) for group 2 and 3 respectively and for group 4 used commercial broiler diet (Quality Feed Ltd.). Total feed intake was similar among the groups. Feed conversion ratios of PL diet, Bio-Sel-E diet, and commercial broiler diet were comparable, and were lower (P<0.05) than the control diet. Significantly higher body weight gain and performance index were found in PL, Bio-Sel-E and commercial broiler diet groups than control diet. The dressing yield of PL diet and commercial broiler diet were comparable, and they were higher (P<0.05) than Control diet and Bio-Sel-E diet. It could be concluded that the Supplementation of 0.5% PL in the diet had positive effect on growth, feed intake, feed conversion ratio, performance index and carcass characteristics of broilers almost similar of Bio-Sel-E and commercial broiler diet. DOI: http://dx.doi.org/10.3329/bjas.v42i2.18492 Bang. J. Anim. Sci. 2013. 42 (2): 123-130